ECONOMIC EFFICIENCY OF THE LAND RESOURCE MANAGEMENT BY AGRICULTURAL PRODUCERS IN THE SYSTEM OF THEIR NON–CURRENT ASSETS ANALYSIS: A CASE STUDY OF THE AGRICULTURAL SECTOR OF UKRAINE - Ruslana SODOMA; Tetiana SHMATKOVSKA; Mykola DZIAMULYCH; Nataliia VAVDIIUK; Nataliia KUTSAI; Vadym POLISHCHUK (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
To assess the effectiveness of the management of land resources for agricultural enterprises suggested factors affecting the market for agricultural products, which integrates a system of environmental, economic and social indicators in this area. The paper highlights main theoretical aspects of the land resource management of the agricultural enterprises. The essence of land resource management is shown based on the definition of the objects of management, which are land resources of agricultural enterprises, subjects of management, which are landowners and employees of such agricultural enterprises, and objective of management, which is providing and maintaining the efficiency of land resources usage as a key factor of agricultural production. The land market and its structure are presented in detail. Described prospects management of land resources of agricultural enterprises. A complete analysis of mortgage lending secured by agricultural lands has been carried out. A decrease in the number of agricultural enterprises, which is mostly connected with imperfections of land governance, formed in the state, has been identified. Relationships between strengths and weaknesses of agricultural enterprises, opportunities, and threats of efficient land use have been identified. Scenarios of economic development have been considered, which should be taken into account while developing a strategy.